Euro's influence upon trade: Rose effect versus border effect - Gianluca Cafiso (European Central Bank (ECB), 2008)
This paper assesses the Euro's influence upon European trade by estimating two different indicators. The first is the so-called “Rose Effect”, while the second is the “Border Effect”. The former measures how much a country within a currency union trades more with its partners than with non-member countries, the latter measures the integration of a country with its trade partners. This study of the Euro's influence by means of the Border Effect is a novelty in the literature, it reveals that the Euro's influence upon trade is not so clear as papers focused only on the Rose Effect claim. This casts doubts about the consequences of the Euro introduction for the European Single Market. Both indicators are estimated by means of a gravity model for bilateral trade flows using a panel of manufacture exports among twenty-four OECD countries.
Keywords: F10; F14; F15; 330; Border Effect; euro; European Integration; Rose effect; Trade; Währungsunion; Euro; Interregionaler Handel; EU-Binnenmarkt; Handelseffekt; Außenhandel mit Industriegütern; EU-Staaten; OECD-Staaten